Finishes work at water features roundabout / Muhammad Nur Aiman Hakimi Mohd Hanafiah - Mohd Hanafiah, Muhammad Nur Aiman Hakimi (Universiti Teknologi MARA, Perak, 2022)
Industrial training give many benefits for the students to gain working experience. The students will be given 20 weeks to complete their industrial training during semester 5 diploma in building. I had be chosen to do my industrial training at Gabungan Strategik Berhad and will be supervised by landscape supervisor, Encik Amir bin Adam and Puan Syifa Binti Awaluddin. Observation and supervision of workers are the ways utilized to accomplish this. This is done when the employees are at work. Reviewing documents and interviewing supervisors and subcontractors are also methods for completing the report's goal. Finally, there are different types of finishes at water features roundabout, each with its own purpose and function in completing the landscape in Pusat Pentadbiran Sultan Ahmad Shah.